Impact of climate change on maize’s water needs, yields and profitability under various water prices in Spain - Rey, D.; Garrido, A.; Mínguez, M. I.; Ruiz-Ramos, M. (Spanish Journal of Agricultural Research, 2011)
<span style="font-size: 11pt; line-height: 115%; font-family: ’TimesNewRomanPSMT’,’serif’; mso-ansi-language: EN-US; mso-bidi-font-family: TimesNewRomanPSMT; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-language: AR-SA;" lang="EN-US">Available water resources are expected to diminish in the Iberian Peninsula as a result of climate change (CC). Agricultural water use represents about 70% of all water uses in Spain. This paper uses a combination of an ensemble of climate change and crop models to analyze the impacts on maize’s water needs, yields and economic profitability under various water prices. Maize’s evapotranspiration (ET), irrigation needs and yield projections under CC are compared with those of current climate in nine sites of Spain. With these simulated data, maize’s and water’s prices are included in a stochastic model to simulate the crop’s net margin, both under CC and current climate conditions. An adaptation strategy potentially useful for maize in Spain is also studied. Results show that such adaptation can reduce negative CC impact on yields. However, decreases in ET and irrigation needs will be lower with than without adaptation. This creates an ambiguous situation which can be affected or solved with water pricing policies. With higher water tariffs, crop’s profitability can drop to negative levels, which may result in the abandoning of the crop in many areas. CC and water policies must be closely coordinated to ensure efficient water use and crops’ profitability.